Banking across borders: Are Chinese banks different? - Cerutti, Eugenio; Casanova, Catherine; Pradhan, Swapan-Kumar (Journal of Banking & Finance, 2023)
Chinese banks have become the largest cross-border creditors for almost half of all emerging market and developing economies (EMDEs). While they look similar to other EMDE banks in terms of ownership and balance-sheet structure, their global cross-border lending resembles that of banks from advanced economies along several dimensions, especially when lending to EMDEs. We find that geographical distance poses a barrier for cross-border lending, including for Chinese banks. For them, given their network of affiliates, this barrier is lower than for other EMDE banks, more like US or European banks. We show that across all bank nationalities, bilateral economic interactions, like trade, FDI and portfolio investment, all positively correlate with cross-border lending. What stands out is that Chinese banks’ lending to EMDEs correlates more than any other nationality with trade, but there is no such correlation with FDI and, unlike all other banks, their lending correlates negatively with portfolio investment.